CCrISP course-Care of critically Ill surgical patient: A critical educational evaluation of the curriculum - Sofi a Anastasiadou (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Introduction: Education is a progressing and changing sector of all sciences. Especially in Medicine and Surgery, education has been evolving rapidly the past century and the changes are evident in strategies, methods, evaluation and assessment. Simulation, 3D encounters and small group sessions are replacing books, long exams and large group teaching lectures in an attempt to keep up with technology and innovation. Methods: CCrISP is a Royal College of Surgeons course about the management of the critically ill surgical patient. Having that as an example, various educational theories and methods are analysed and presented in the following article.